Pre-development denudation rates for the Great Barrier Reef catchments derived using 10Be. (November 2021) - Mariotti, Apolline; Croke, Jacky; Bartley, Rebecca; Kelley, Samuel E.; Ward, Jay; Fülöp, Réka-Hajnalka; Rood, Anna H.; Rood, Dylan H.; Codilean, Alexandru T.; Wilcken, Klaus; Fifield, Keith
Abstract: Understanding of the pre-development, baseline denudation rates that deliver sediment to the Great Barrier Reef (GBR) has been elusive. Cosmogenic 10 Be in sediment is a useful integrator of denudation rates and sediment yields averaged over large spatial and temporal scales. This study presents 10 Be data from 71 sites across 11 catchments draining to the GBR: representing 80% of the GBR catchment area and provide background sediment yields for the region. Modern, short-term, sediment yields derived from suspended load concentrations are compared to the 10 Be data to calculate an Accelerated Erosion Factor (AEF) that highlights denudation "hot-spots" where sediment yields have increased over the long-term background values. The AEF results show that 58% basins have higher modern sediment yields than long-term yields. The AEF is considered a useful approach to help prioritise on-ground investments in remediation and the additional measured empirical data in this paper will help support future predictive models.